PENGARUH HARGA, PROMOSI DAN E-SERVICE QUALITY TERHADAP MINAT BELI ULANG KONSUMEN PADA APLIKASI GRAB - Rachmansyah Putra Herwananto, (2022)
Technological developments in today's modern era bring changes in the field of transportation. Many online-based transportation service businesses have sprung up, one of which is Grab. This study aims to determine the effect of price, promotion and e-service quality on consumer repurchase intention on the Grab application. The method of determining the sample to be used in this study is non-probability sampling with purposive sampling with a total of 100 respondents. Data collection is done through Google Form. Data analysis was performed using the PLS (Partial Least Square) method using SmartPLS 4.0 software. The results of the data analysis show that: (1) price has a positive and significant effect on consumer repurchase intention on the Grab Application, (2) promotion has a positive and significant effect on consumer repurchase intention on the Grab Application, (3) e-service quality has a positive and significant impact on consumer repurchase interest in the Grab Application.